Cognitive Processes Related to Memory Capacity Explain Nearly All of the Variance in Language Test Performance in School-Age Children With and Without Developmental Language Disorder - Gillam, Ronald B.; Serang, Sarfaraz; Montgomery, James W.; Evans, Julia L. (Frontiers in Psychology, 2021)
The purpose of this study was to investigate the dimensionality of the cognitive processes related to memory capacity and language ability and to assess the magnitude of the relationships among these processes in children developing typically (TD) and children with developmental language disorder (DLD). Participants were 234 children between the ages of 7;0 and 11;11 (117 TD and 117 DLD) who were propensity matched on age, sex, mother education and family income. Latent variables created from cognitive processing tasks and standardized measures of comprehension and production of lexical and sentential aspects of language were tested with confirmatory factor analysis and structural regression. A five-factor CFA model that included the constructs of Fluid Intelligence, Controlled Attention, Working Memory, Long-Term Memory for Language Knowledge and Language Ability resulted in acceptable model fits. The four cognitive abilities accounted for more than 92% of the variance in the language measures. A structural regression model indicated that the relationship between working memory and language ability was significantly greater for the TD group than the DLD group. These results are consistent with a broad conceptualization of the nature of language impairment in older, school-age children as encompassing a dynamic system in which cognitive abilities account for nearly all of the variance in linguistic abilities.